Research on the impact of coupling and coordination of rural consumption power system on the consumption of rural residents in China - Tian, Zhen; Wang, Rui; Tan, Yan; Chen, Zhaoqin (PLOS ONE, 2025)
The harmonious operation of social consumption power system can stimulate residents’ higher-level consumption demands, thereby driving overall consumption growth. Based on the panel data of 30 Chinese provinces (excluding Hong Kong, Macao, Taiwan, and Tibet) from 2002 to 2022, this study integrates multiple determinants of rural residents’ consumption into the conceptual framework of social consumption power. Employing a systematic approach, we construct a spatial Durbin model to empirically examine how the coupling coordination level of the rural consumption power system influences rural residents’ consumption behavior. The findings reveal that the coupling coordination level of rural consumption power system exerts a statistically significant positive effect on rural residents’ consumption not only within a given province but also in neighboring provinces, indicating spatial spillover effects. These spillover effects are particularly pronounced in the eastern and central regions. Therefore, in order to release the huge consumption potential in rural areas, it’s vital to make good use of the coupling and coordinating role of the three subsystems of consumption subject, consumption object and consumption environment and achieve the fit and coordination between supply-side structural reform and demand-side structural reform. The research findings not only provide factual evidences and theoretical support for transforming the government’s strategy of expanding rural residents’ consumption but also propose practical instructions for further releasing rural residents’ consumption potential in the new era.